“Looking Glass:” Reflections on Mirrors and Transparency as Devices for Representation in Visual Arts (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
Today the locution “looking glass” survives almost exclusively thanks to the extraordinary success of Lewis Carroll’s novel Through the Looking-Glass. This expression underlines the ambiguity between the glass surface intended as a device through which we can see the world or as an actual object to be “looked at.” Apparently, the early Renaissance perspective window, thanks to the mildness of the Mediterranean climate, did not need any panes. And certainly, even when glass panes are there, they are usually not reproduced in painting. The glass main virtue is its transparency, which makes it almost invisible. Something similar happens with other “glasses” specifically made to look through them: the drinking glass and the lens. Glass panes appear to sight only when different practical needs come into play, as in perspective drawing machines, or when its transparency is contradicted by a precise action that compromises or denies it: when panes are broken, as in this enigmatic portrait of early XIX c., or voluntarily covered, like for a blackout, as in Duchamp’s Fresh Widow. Looking through the glass, looking at the image reflected in the mirror and, finally, looking at the glass itself, as a device for presenting and representing spaces, are three recurring attitudes in the work of Italian artists of the late 20th century, like Lucio Fontana and Luciano Fabro.
Keywords: mirrors; glass; XIX and XX c. visual art; photography; conceptual art